Peran Anggaran dalam Pengelolaan Risiko Keuangan Perusahaan - Anwar, Ravel; Marliani, Sonnya (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2024)
Amid rising economic uncertainty, this study explores the strategic role of budgeting in managing corporate financial risk. It examines budgeting as a critical management tool for identifying, mitigating, and controlling risks within a business environment. Utilizing a qualitative approach grounded in literature review, data is gathered from prior studies to demonstrate the positive impact of a well-structured and flexible budget. Findings reveal that companies capable of integrating risk management into their budgeting processes are more likely to mitigate impacts from market, credit, liquidity, and operational risks. Additionally, various studies suggest that adaptive budgeting enhances a company’s resilience in responding to market fluctuations. This study also highlights specific strategies, such as contingency planning and reserve allocation, which effectively support financial stability. These findings contribute to financial management literature while providing practical guidance for companies to optimize budgets as strategic tools for addressing economic challenges. Future research is recommended to broaden the scope across sectors and undertake longitudinal analysis to deepen understanding of budgeting’s role in financial risk management